Cancer frequency: Kars province - Adalı, Yasemen; Güvendi, Bülent; Toyran, Tuğba; Fındık Güvendi, Gülname (International Journal of Research in Medical Sciences, 2019)
Background: Malignant tumors are important causes of mortality and morbidity in the world. It is known that the incidence of tumors- in which a large number of etiologic agents are identified and continued to be investigated- varies according to age, gender and geographical location. This study aimed to determine the prevalence and localization distributions of malignant tumors in Kars. Methods: The study included 17012 patients whose biopsy materials were evaluated in the Department of Pathology of Kafkas University Health Research and Practice Hospital between 2014-2017. Results: The mean age of all cancer cases was 63.3±14.8 and the median age was 63. The cancer frequency was detected 22.6% in 2014, 23.3% in 2015, 26.9% in 2016 and 27.2% in 2017 with general slight male dominance. Conclusions: The incidence of cancer in our country is found to be lower compared to the world data. It is necessary to examine and take into account the regional and city-based cancer statistics that serve as an important key stone in the planning of health policies and health investments in our country. Regional data is not only important for treatment services, but also for preventive health services and early diagnosis.